Pengaruh C-Phycocyanin Terhadap Kadar Soluble Glikoprotein (Sgp130) Pada Trofoblas Tikus Wistar Yang Dipapar Interleukin-6 (IL-6) - Elizabeth Haryanti; Harry K Gondo (Universitas Wijaya Kusuma Surabaya, 2017)
The placenta is a joint organ of the uterus surface mother and fetus. One of cytokines of the placenta is IL-6 which is essential for normal placental development and successful pregnancy. Sgp130 binds Interleukin-6-sIL-6R complex, so Interleukin-6 signal cannot be passed on. Both factors play an important role in pre-eclampsia which has high levels of IL-6 and sgp130. They are expected to be suppressed by administration of C-phycocyanin. The aim of this study to prove effect of C-phycocyanin on sgp130 levels among wistar rats’ trophoblasts exposed to IL-6. The design of the study was Experiment, Post Test Only Control, analyse with One way Anova. The samples were 25 rats divided four treatment groups. Dose of C-Phycocyanin (10mg, 20mg, 40mg). The results significant difference between control and treatment group IL-6, IL-6 + CPC10, IL-6 + CPC20. But there was no significant difference between control group and IL-6 + CPC40, sig value. 0.214 (sig. <0.05). Conclusion. There is an effect of C-Phycocyanin on Sgp130 levels in wistar rats’ trophoblasts exposed to IL-6 at a dose of C-Phycocyanin 40mg.